195k views
4 votes
This is expansion of Polynomial products and I just have to expand it but I dont know how to do it.

This is expansion of Polynomial products and I just have to expand it but I dont know-example-1
User Mijin
by
5.7k points

1 Answer

5 votes

Answer:

The expanded form of
(x-(2)/(x) )  =  ((x+\sqrt2)(x-\sqrt2))/(x)

Explanation:

Here, the given expression is
(x-(2)/(x) )

Expanding the given :


(x-(2)/(x) ) = (x^2-2)/(x)

Now, by ALGEBRAIC IDENTITY:


(a+b)(a-b) =  a^2 - b^2\\\implies(x^2-2)  = (x-\sqrt2)(x+\sqrt2)

So, the given expression becomes,


(x^2 -2)/(x)  = ((x+\sqrt2)(x-\sqrt2))/(x)

Hence, the expanded form of
(x-(2)/(x) )  =  ((x+\sqrt2)(x-\sqrt2))/(x)

User Naomy
by
5.7k points